2016
DOI: 10.1021/acs.joc.5b02887
|View full text |Cite
|
Sign up to set email alerts
|

Substituent-Controlled Chemoselective Cleavage of C═C or Csp2–C(CO) Bond in α,β-Unsaturated Carbonyl Compounds with H-Phosphonates Leading to β-Ketophosphonates

Abstract: An unprecedented substituent-controlled chemoselective cleavage of C═C double bond or C(sp(2))-C(CO) bond along with aerobic phosphorylation of α,β-unsaturated carbonyl compounds with H-phosphonates through a radical process has been disclosed. The current strategy provides an access to β-ketophosphonates under mild conditions with a wide substrate scope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 57 publications
0
17
1
Order By: Relevance
“…The reaction mixture was then stirred for 8–20 h at 60 °C. Upon completion of the reaction, the mixture was concentrated in vacuum and purified by chromatography on silica gel (ethyl acetate: n ‐hexane = 2:1) to afford the β‐ketophosphine oxides 3 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction mixture was then stirred for 8–20 h at 60 °C. Upon completion of the reaction, the mixture was concentrated in vacuum and purified by chromatography on silica gel (ethyl acetate: n ‐hexane = 2:1) to afford the β‐ketophosphine oxides 3 …”
Section: Methodsmentioning
confidence: 99%
“…In general, β‐ketophosphine oxides are synthesized by the Arbuzov‐type reactions of α‐halogenated ketones and the α‐acylation of alkylphosphine oxides . Various studies have reported on a number of methods based on the transition metal‐catalyzed phosphorylation of alkenes and their derivatives, such as cinnamic acids, allyl alcohols, cinnamyl/alkynylcarboxylates, carbonyl compounds, and alkynes . Recently, Yu et al .…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the difunctionalization reaction of unsaturated hydrocarbons such as alkenes or alkynes has attracted great interests of chemists in the construction of various valuable organic compounds because of its high efficiency in the cascade formation of carbon-carbon and carbon-heteroatom bonds. Recently, the oxyphosphorylation of alkenes, [4] alkynes, [4b,5] cinnamic acids, [6] alkynylcarboxylic acids, [5d,7] cinnamyl/alkynylcarboxylates, [8] and α,β-unsaturated carbonyl compounds [9] with P(O)-H compounds and dioxygen has emerged as a fascinating and powerful protocol for the synthesis of β-ketophosphine oxides/β-ketophosphonates, which are an important class of phosphorus-containing compounds especially used as key synthetic precursors to access olefins via the well-known Horner-Wadsworth-Emmons (HWE) reaction. [10] Despite the significance of these reactions, the development of simple, convenient and efficient alternative oxyphosphorylation strategy to access to β-ketophosphine oxides/β-ketophosphonates is still highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…In this domain, the groups of Dong, Cheng, and Zhang described the functionalization of C–C­(CO) bonds (Scheme A). With regard to the more challenging triple CC bond cleavage owing to the weaker polarization, there are far fewer results, generally delivering linear molecules. Likewise, the appealing and challenging synergistic merger of C–H functionalization with CC bond cleavage is in infancy.…”
mentioning
confidence: 99%